PENGARUH SHIFT KERJA TERHADAP KELELAHAN KERJA PERAWAT DI UNIT RAWAT COVID-19 RSUD dr. DJASAMEN SARAGIH - Muhraza Siddiq; Armanda Prima; Novrika Silalahi; Ripai Siregar; Sulastri Br Ginting (Jurnal Kesehatan Masyarakat dan Lingkungan Hidup, 2021)
Work weakness is portion of the common probelms that are regulary experienced within the work constrain, wearness can significantly affect the health of the workforce and can reduce productivity, including the nurse workforce. Fatigue is often caused by inappropriate working hours. Shift workers tend to be more prone to work burnout. Impactof work shift on nurse's work weakness in the unit covid-19 roomRSUD dr. Djasamen Saragih. The study used quantitative research with observational methods on 34 respondents. Univariat analysis showed that the majority of respondents experienced work fatigue, namely 20 people (58.8%) and not tired of work, namely 14 people (41.2%). From the results of the Bivariate analysis between work shifts and work weakness using the Chi-Square test, the p-value is 0.005. With p-value (0.005)<(0.05). This H0 is rejected and H1 is accepted. There’s an effect of work shifts on the work fatigue of nurses in the Covid-19 Inpatient room at dr. Djasamen Saragih in 2021.